ANALISIS KESULITAN BERPIKIR VISUAL DALAM MEMAHAMI KONSEP PADA MATERI HIMPUNAN - Milla, Meriana Loru; Patricia, Firda Alfiana; Sari, Raras Kartika (Universitas Insan Budi Utomo, 2018)
Mathematics is a lesson that is always a reference to intelligence and completeness of the process of student education anytime and anywhere. The research aims to analyze the difficulties in the seventh grade students of SMP 4 Wewewa Timur in understanding the concept of mathematical material, namely set. This research is included in the type of descriptive qualitative research. The research subjects were six students. Instruments in the process of collecting data are interview guidelines and question test sheets. This study uses data collection techniques including test methods, interview methods, and documentation. The results of the research process found that the difficulty of class VII students of SMP Negeri 4 Timur in solving questions in the set material as follows: 1) difficulty using the concept; 2) difficulties in carrying out basic mathematical operations and addition and subtraction operations; 3) difficulty understanding the problem of the story and determining the things needed to solve the problem. Student difficulties are caused by several factors, namely 1) internal factors, causes of difficulties that originate from within the student itself; and 2) external factors, student difficulties caused and originating from outside the student. Based on the results of the interview test the factors that influence students and become the cause of student learning difficulties are: 1) low capacity or intelligence of students; 2) not confident, 3)mathematics learning disabilities; 4) learning disability and 5) the influence of the environment around students.